Patterns of per- and polyfluoroalkyl substance occurrence in fish in the 2018–2019 U.S. EPA National Rivers and Streams Assessment - Wathen, John B.; Contreras Balbuena, Andrea C. (The Science of the total environment, 2025)
The purpose of this study is to further elucidate patterns of occurrence of PFAS compounds in the tissue of freshwater fish in major U.S rivers beyond those derived from the usual statistics. Per- and poly-fluoroalkyl substances (PFAS) are a group of synthetic organic chemicals that have become widely distributed in the environment since their introduction in the 1940s. The characteristics of individual compounds that influence their nature include the number of carbon atoms saturated with fluorine in the molecule chain, and whether they are carboxylates, sulfonates, or other forms. Perfluorooctane sulfonate (PFOS), perfluoro-undecanoic acid (PFUnA), perfluorodecanoic acid (PFDA), perfluorododecanoic acid (PFDoA), perfluoro-nonanoic acid (PFNA), perfluorooctanoic sulfonamide (PFOSA) [both surveys], perfluorotridecanoic acid (PFTrDA), perfluorotetradecanoic acid (PFTeDA), and perfluorodecanoic sulfonate (PFDS) [2018–2019 only] have been found to occur in fish in major U.S. rivers in EPA surveys in 2013–2014 (n = 353 samples) and 2018–2019 (n = 290), in repeatable patterns of combinations, averaging 5.2 compounds per sample (2018–2019 Survey). Concentrations of at least one of these compounds were detected in over 90 % of composite samples in both surveys, and 96 samples (35 %) contained 7 or more compounds in the 2018–2019 survey. Rates of decline in compound concentrations in fish tissue in the 5 years between the surveys, ranging from 20 % to 57 %, were inversely proportional to the number of fluorine-saturated compounds in the individual compound chains. Other factors are described, such as repeating patterns of elevated PFAS concentrations, geographic occurrence, and elevated PFAS fish tissue concentrations geographically co-incident to locations with environmental justice concerns. Molecules: Pubchem The graphical abstract is a picture of a fish constructed from depictions of the molecules of the nine PFAS compounds that are the subject of this analysis, drawn from PubChem. [Display omitted] •Nine PFAS compounds occur in >20 % of freshwater fish in major U.S. rivers.•PFOS, PFUnA, PFDA, PFDoA and PFTrDA predominate.•Concentrations declined inversely proportional to carbon chain length.•Over five years, PFOS declined 57 %, PFDA 41 %, PFUnA 32 %, and PFDoA 20 %.